Long-term outcomes of His bundle pacing in patients with heart failure with left bundle branch block - Huang, Weijian; Su, Lan; Wu, Shengjie; Xu, Lei; Xiao, Fangyi; Zhou, Xiaohong; Mao, Guangyun; Vijayaraman, Pugazhendhi; Ellenbogen, Kenneth A (Heart (British Cardiac Society), 2019)
ObjectivesHis bundle pacing (HBP) can potentially correct left bundle branch block (LBBB). We aimed to assess the efficacy of HBP to correct LBBB and long-term clinical outcomes with HBP in patients with heart failure (HF).MethodsThis is an observational study of patients with HF with typical LBBB who were indicated for pacing therapy and were consecutively enrolled from one centre. Permanent HBP leads were implanted if the LBBB correction threshold was <3.5V/0.5 ms or 3.0 V/1.0 ms. Pacing parameters, left ventricular ejection fraction (LVEF), left ventricular end-systolic volume (LVESV) and New York Heart Association (NYHA) Class were assessed during follow-up.ResultsIn 74 enrolled patients (69.6±9.2 years and 43 men), LBBB correction was acutely achieved in 72 (97.3%) patients, and 56 (75.7%) patients received permanent HBP (pHBP) while 18 patients did not receive permanent HBP (non-permanent HBP), due to no LBBB correction (n=2), high LBBB correction thresholds (n=10) and fixation failure (n=6). The median follow-up period of pHBP was 37.1 (range 15.0–48.7) months. Thirty patients with pHBP had completed 3-year follow-up, with LVEF increased from baseline 32.4±8.9% to 55.9±10.7% (p<0.001), LVESV decreased from a baseline of 137.9±64.1 mL to 52.4±32.6 mL (p<0.001) and NYHA Class improvement from baseline 2.73±0.58 to 1.03±0.18 (p<0.001). LBBB correction threshold remained stable with acute threshold of 2.13±1.19 V/0.5 ms to 2.29±0.92 V/0.5 ms at 3-year follow-up (p>0.05).ConclusionspHBP improved LVEF, LVESV and NYHA Class in patients with HF with typical LBBB.